2020
DOI: 10.1109/mra.2019.2963161
|View full text |Cite
|
Sign up to set email alerts
|

Sewing up the Wounds: A Robotic Suturing System for Flexible Endoscopy

Abstract: If a perforation occurs as a result of a flexible endoscopic procedure, suturing through urgent laparoscopy or open surgery may be required to repair the perforation because suturing is normally stronger than closure using existing endoscopic devices. Suturing with stitches and knots, widely adopted in open or laparoscopic surgery, is still not possible in flexible endoscopy. This is because of the confined space of the natural orifice and target area, high levels of motion dexterity and force needed for stitc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…Through the pilot animal study, we demonstrated that our novel endoscopic robotic device can be used to suture perforations, and potentially suture bleeding sites and achieve hemostasis in ESD, without the need for additional surgical interventions. 13…”
Section: How We Can Use Robotics To Manage Iatrogenic Complications Amentioning
confidence: 99%
“…Through the pilot animal study, we demonstrated that our novel endoscopic robotic device can be used to suture perforations, and potentially suture bleeding sites and achieve hemostasis in ESD, without the need for additional surgical interventions. 13…”
Section: How We Can Use Robotics To Manage Iatrogenic Complications Amentioning
confidence: 99%
“…6 The robotic needle holder is a modified grasper with two needle holes that can lock and release a double-pointed lancet needle attached to a suture. 7 ISIS-Scope/STRAS System. The ISIS-Scope/STRAS System (Karl Storz, IRCAD, Tuttlingen, Germany) is a flexible robotic system based on a modified shortened version of the manual Anubiscope.…”
Section: Robotic Endoscopic Platformsmentioning
confidence: 99%
“…This is in contrast to currently available endoscopic suturing devices, such as OverStitch, which relies on fastening elements. 7 In our animal trial, we used the Endomaster EASE System to perform a 10 mm submucosal incision in the colon. We then used the robotic needle holder and robotic grasper to apply a Figure-of-8 stitch.…”
Section: Use Of Robotic Endoscopy In Conventional Therapeutic Endoscomentioning
confidence: 99%
See 2 more Smart Citations